Political Bias in the Media's Coverage of Firms' Earnings Announcements - Rees, Lynn; Twedt, Brady J. (The Accounting Review, 2022)
ABSTRACT This study examines whether firms' political activism induces bias in the media coverage of earnings announcements and how such coverage impacts markets. We infer firm political ideology based on employee political contributions and identify firm and manager characteristics associated with distinct ideologies. We find that media outlets negatively slant their coverage of earnings announcements when the political leanings of the outlet are incongruent with the political ideology of the firm. Consistent with slanted coverage affecting market outcomes, we provide evidence that the price reaction to good (bad) earnings news is decreasing (increasing) in the percent of incongruent media outlets covering the earnings announcement. In addition, trading volume and returns volatility are decreasing for good earnings news with the percent of incongruent media outlets. Our results suggest that the prevalent bias across some media outlets in their coverage of political news also affects their coverage of corporate financial events. JEL Classifications: G14; L82; M41.